PENGARUH BELANJA LANGSUNG DAN BELANJA TIDAK LANGSUNG TERHADAP PERTUMBUHAN EKONOMI PROVINSI KALIMANTAN TIMUR - MUHAMMAD ADNAN PALAGUNA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
Based of the results of the analysis are known, that there was a significant correlation between direct expenditure and indirect expenditure on economic growth in East Kalimantan in 2005-2014. Based on f–test statistic (simultaneously test) found that simultaneously direct expenditure and indirect expenditure have a significant effect on economic growth in East Kalimantan in 2005 - 2014 with a significan level of 0,000. Based on t-test (partial test) found that direct spending partially has significant impact on economic growth at 0,039 significan level. While partially indirect spending does not have significant impact on economic growth in East Borneo with a significan level of 0,501.Keywords: Direct Spending, Indirect Spending, Economic Growth.